2019
DOI: 10.1101/753418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The versican-hyaluronan complex provides an essential extracellular matrix niche for Flk1+ hematoendothelial progenitors

Abstract: Extracellular matrix aggregates comprising the proteoglycan versican and glycosaminoglycan hyaluronan are necessary for cardiac development. Here we identify failure of primary vascular plexus formation and attenuation of primitive hematopoiesis in the yolk sac of the mouse insertional mutant Vcan hdf , which lacks all versican isoforms. Spatially co-regulated versican and hyaluronan were intimately associated with Flk1+ hematovascular progenitor cells migrating from the primitive streak into extraembryonic me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…This notion was corroborated by a recent study showing that HA glycosaminoglycans are closely associated with early Flk1 + hematoendothelial cell progenitors during gastrulation and act as a cytokine trap to enhance VEGF-mediated angiogenesis and primitive hematopoiesis. 71 Our previous data have shown that kitlgb-kitb signaling is essential for maintaining runx1 expression and HSPC specification in the HE. 27 However, we and others 64 have demonstrated that kitlgb is highly expressed in the posterior blood island but not in the aortic HE region.…”
Section: Discussionmentioning
confidence: 95%
“…This notion was corroborated by a recent study showing that HA glycosaminoglycans are closely associated with early Flk1 + hematoendothelial cell progenitors during gastrulation and act as a cytokine trap to enhance VEGF-mediated angiogenesis and primitive hematopoiesis. 71 Our previous data have shown that kitlgb-kitb signaling is essential for maintaining runx1 expression and HSPC specification in the HE. 27 However, we and others 64 have demonstrated that kitlgb is highly expressed in the posterior blood island but not in the aortic HE region.…”
Section: Discussionmentioning
confidence: 95%
“…Prior work had showed accumulation of ADAMTS9 substrates versican and fibronectin in the ECM of ADAMTS9 mutant D12 cells when compared to the parental RPE-1 cells (12, 34). Both substrates are relevant to cell adhesion, with versican being anti-adhesive (35-37) and fibronectin being pro-adhesive (38, 39).…”
Section: Resultsmentioning
confidence: 99%
“…Versican had previously emerged as a key anti-adhesive ADAMTS9 substrate in human myometrial SMCs, since they formed few focal adhesions after ADAMTS9 knockdown and versican accumulated in Adamts9-deficient mouse myometrium; moreover, focal adhesions were restored dramatically by versican knockdown concomitant with ADAMTS9 knockdown in human myometrial SMCs (14). Versican, which also accumulates in the ECM of D12 cells when cultured for 72 h or longer (12,34), is likely also relevant to altered adhesion of D12 cells, although the possibility was not specifically experimentally addressed here. MT1-MMP knockdown had a restorative effect on fibrillar adhesion formation by D12 cells, suggesting that the complex tissue and cell phenotypes resulting from ADAMTS9 and ADAMTS20 deficiency reflect the impaired cleavage of more than one substrate, i.e., MT1-MMP, versican and potentially others.…”
Section: Discussionmentioning
confidence: 99%
“…Acting as a transmembrane protein, TMEM2 is associated with tumor invasion and angiogenesis [28,29] and manipulates cell adhesion and metastasis by degrading nonprotein components of the extracellular matrix [30]. Gastric cancer prognosis is positively related to GUCY1A2 [31], which plays a vital role in rheumatoid arthritis development [32], and afects SARS-CoV 2 infections and drug repurposing [33].…”
Section: Discussionmentioning
confidence: 99%